Vulval cancer incidence, mortality and survival in England: age‐related trends. (22nd October 2013) - Lai, J; Elleray, R; Nordin, A; Hirschowitz, L; Rous, B; Gildea, C; Poole, J
<x xml:space="preserve">Abstract</x> Objective To explore the trends and age characteristics of vulval cancer incidence, mortality, survival and stage of disease. Design Retrospective population‐based observational study based on cancer registry and Office for National Statistics data. Setting England. Population All women diagnosed with vulval cancer, defined by the site of the tumour (ICD‐10 code C51). Methods Including all C51 cases, Poisson regression was used to test for trends in incidence and mortality rates, and generalised linear modelling was used to test for trends in relative survival. Excluding women with melanomas, basal cell carcinomas and Paget disease, stage was investigated as a percentage of staged data by age. Main outcome measures Age‐standardised incidence and mortality rates, relative survival rates and stage of disease at diagnosis. Results From 1990, there was a statistically significant increase in overall incidence (P = 0.018) and decrease in mortality (P < 0.001). In addition, there were statistically significant increases in overall survival (1‐year, P < 0.001; 5‐year, P < 0.001). However, from 1990, incidence increased in women aged 20–39 years (P = 0.002), 40–49 and 50–59 years (both P < 0.001) and 60–69 years (P = 0.030) and decreased in women aged 80 years and above (P < 0.001). There were statistically significant decreases in mortality in women aged ≥60 years (P < 0.001), and statistically significant increases in 1‐year survival in women aged ≥40 years (P ≤ 0.047) and in 5‐year survival in women aged 40–49 and ≥60 years (P ≤ 0.011). Stage patterns by age highlight diagnosis at an earlier stage in younger women and more advanced stage diagnosis in older women. Conclusion Survival from vulval cancer has improved and mortality has decreased since 1990. The overall incidence of disease has increased as a result of more new diagnoses in the under 70‐year age group.